If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 = -12x Reorder the terms: 4 + 2x = -12x Solving 4 + 2x = -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 4 + 2x + 12x = -12x + 12x Combine like terms: 2x + 12x = 14x 4 + 14x = -12x + 12x Combine like terms: -12x + 12x = 0 4 + 14x = 0 Add '-4' to each side of the equation. 4 + -4 + 14x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 14x = 0 + -4 14x = 0 + -4 Combine like terms: 0 + -4 = -4 14x = -4 Divide each side by '14'. x = -0.2857142857 Simplifying x = -0.2857142857
| 20*log(x)=120 | | 20log(x)=120 | | 9x+27=3x+2 | | -12=42-9x | | 2x-2=10x+10 | | 8-2x=-46 | | 7x+31=61-3x | | x^2+10=6*x | | 6(5w-5)=-31(3-w) | | t=25+8.25w | | 0.03(y+8)=0.01(6y+3)-0.21 | | 15x=22.5 | | 45/-34 | | x+y+z=30thens | | 53-x=x+35 | | 3y+8=6y+3-21 | | 7a-4-(a+3)= | | x^3-3X=589 | | -34/45 | | d(10cos6000t)/dt | | (8x-15)+(2x+25)=180 | | 5(3n-2)-11n=2n-1 | | .75x+-34=.5 | | 2-6(6-2x)=0 | | x^4+2x^2-100=0 | | (y+10)*5=15*5 | | 8x-2(3x-9)=10 | | 3-4(2x+7)=6 | | 7/8=q/11 | | z/9=9/5 | | 8/11=n/3 | | 5x+3.75=10 |